Prevalence and associated risk factors of hypertension amongst adults in a rural community of Limpopo Province, South Africa - Samuel T. Ntuli; Eric Maimela; Mariannes Alberts; Solly Choma; Sekgothe Dikotope (AOSIS, 2015)
Background: Hypertension is problem already faced by urban populations of South Africa, but little is known about its prevalence and risk factors in rural areas. Aim: To assess the prevalence of and risk factors associated with hypertension amongst adults in a rural community in South Africa. Setting: Dikgale Health and Demographic Surveillance Site, Limpopo Province, South Africa. Methods: A community-based cross-sectional survey was carried out at this site where individuals aged 15 years and older were screened using a locally adapted version of the World Health Organization STEPwise questionnaire. Demographics, anthropometry and three independent blood pressure (BP) readings were taken. The average of the three BP measurements was used in analysis, and hypertension taken as systolic and diastolic BP of ≥ 140 or ≥ 90 mmHg respectively, or at least a two-week history of antihypertensive treatment. Analysis included the Chi-square test and statistical significance was set at p ≤ 0.05. Results: A total of 1407 individuals were interviewed, of whom 1281 had complete BP, weight and height measurements taken. The mean age of participants was 44.2 ± 2 0.9 years (range 15-98 years), 63% were female, 55% were single and 90% were unemployed, whilst 13% were tobacco smokers and 20% reported drinking alcohol. Overall prevalence of hypertension was 41% and this was significantly associated with age and marital status. Conclusion: The prevalence of hypertension was found to be high. Prevention strategies are urgently needed to address this life-threatening and important risk factor for cardiovascular disease in rural Limpopo Province.